THE EXISTING ROLES OF LITERACY TEACHERS IN THE ERA OF MULTILITERACIES: A SOCIOCULTURAL PERSPECTIVES - Rama Dwika Herdiawan (Universitas Majalengka, 2021)
Abstract. Literacy is defined traditonally as ‘the ability to read and write’ and it is also regarded as the ability to understand every single iinformation in different contexts or fields. Nevertheless, the new literacy approach in the point of view of the post-structuralism covers the representation of texts in context, different values, meanings and the principles of multiliteracies. Traditional and modern concepts of literacy have correlation with a number of sociocultural activities which occurs in the in the society as well as the classroom which represents a social space. This study focuses on explaining the term literacy and multiliteracies in the postmodern world and also the existing roles of literacy teachers for the practical activities in Indonesian literacy classrooms. Keywords: Literacy Teachers, Multiliteracies, Sociocultural Perspectives